2018
DOI: 10.24093/awej/vol9no1.28
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Vocabulary Knowledge in Speaking Development of Saudi EFL Learners

Abstract: Speaking in a foreign language is considered to be a challenging aspect of language learning that demands competence and mastery in learning any foreign language. Vocabulary learning verifies to play an important role in oral communication. However, literature lacks the studies where both English as a foreign language (EFL) students and teachers' views are obtained to provide analyses of the situations in which learners are not showing desired results in speaking. The current study explores the problems of lac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 0 publications
6
73
0
3
Order By: Relevance
“…The students with large vocabulary performed comparably with the students with much smaller vocabulary in speaking activities. In line with Seffar (2015) and Khan (2018) found that both teacher and learners indicated vocabulary deficiency as the major factors in students' inability to speak English.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The students with large vocabulary performed comparably with the students with much smaller vocabulary in speaking activities. In line with Seffar (2015) and Khan (2018) found that both teacher and learners indicated vocabulary deficiency as the major factors in students' inability to speak English.…”
Section: Discussionsupporting
confidence: 69%
“…There were several studies that conducted about vocabulary and speaking in the past. Seffar (2015) and Khan (2018) analysed teacher and students' perception of the role of vocabulary and students' speaking performance. Moreover, Fhonna (2014), Yuwinda (2015) and Uzer (2017) have conducted the study to investigate the correlation between vocabulary mastery and English-speaking ability for senior high school students.…”
Section: A Introductionmentioning
confidence: 99%
“…On the other hand, the subject of how the co-occurrence of different types of assessment contributes to the improvement of student learning has received less attention, particularly research that focuses on different higher education institutions. Khan, Radzuan, Shahbaz, Ibrahim and Mustafa (2018) asserted that technology is playing its part in the development of language learning and various researchers are using technology in teaching and learning language (Khan, Radzuan, Alkhunaizan, Mustafa, & Khan, 2019;Shahbaz & Khan, 2017); thus the role of continuous assessment is vital. There is a gap in the literature in relation to studies that compare the students from the English Language Department across different higher education institutions on the relationship between assessment and student learning.…”
Section: Background Of the Studymentioning
confidence: 99%
“…The greater the vocabulary knowledge, the higher speaking proficiency learners have. Khan, Radzuan, Shahbaz, Ibrahim and Mustafa (2018) prove that there is "a strong correlation between speaking proficiency and vocabulary knowledge" (p. 414). This means that there is a direct proportion between vocabulary and language proficiency.…”
Section: Vocabulary and Grammar For Speakingmentioning
confidence: 90%